2004
DOI: 10.1136/jcp.2004.016576
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of tenascin-C expression in superficial and invasive bladder cancer

Abstract: Aims:Tenascin-C (Tn-C) is an extracellular matrix glycoprotein that is upregulated in malignant tumours. Tn-C promotes cell growth, cell migration, and angiogenesis. It has been suggested to be a prognostic factor in various types of malignant tumours, but there is little information on its significance in bladder cancer with regard to overall survival (OS) and recurrence free survival (RFS).Methods:Tn-C expression was studied in 106 patients with bladder cancer diagnosed between 1994 and 1997. Immunohistochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 32 publications
2
33
0
1
Order By: Relevance
“…Z badań [71] poświęconych ocenie znaczenia tenascyny C w raku pęcherza moczowego wynika, że lokalizacja i wzór ekspresji TN-C w komórkach nowotworowych mają znaczenie prognostyczne i potencjalnie mogą zostać wykorzystane do wykrywania nowotworów o tym umiejscowieniu.…”
Section: Kliniczne Znaczenie Tenascyny C W Nowotworach Układu Moczowounclassified
“…Z badań [71] poświęconych ocenie znaczenia tenascyny C w raku pęcherza moczowego wynika, że lokalizacja i wzór ekspresji TN-C w komórkach nowotworowych mają znaczenie prognostyczne i potencjalnie mogą zostać wykorzystane do wykrywania nowotworów o tym umiejscowieniu.…”
Section: Kliniczne Znaczenie Tenascyny C W Nowotworach Układu Moczowounclassified
“…In many cancer forms, such as breast [14, 15], lung [16], brain [17], urological [18, 19], malignant melanoma [20], pheochromocytoma [21], cholangiocarcinoma [22] and adipocytic tumors [23], a high tenascin-C expression has been correlated with a poor patient survival [5, 6]. While this correlation applies to some cancers, there are also reports where tenascin-C expression correlates with a lower stage of disease and a better patient outcome [5, 6, 24, 25].…”
Section: Introductionmentioning
confidence: 99%
“…CAFs in the stroma of invasive carcinoma continue depositing large amounts of ECM, including tenascin C in some cases (Chiquet-Ehrismann et al 1986;Inaguma et al 1988). It has been shown that in breast and bladder carcinomas expression of tenascin C correlates with increased tumor invasiveness (Mackie et al 1987;Brunner et al 2004). The accumulation of ECM in tumors contributes to increased interstitial fluid pressure which hinders oxygen and nutrient diffusion (Netti et al 2000;Brown et al 2004).…”
Section: Tumor Microenvironment In Regulating Angiogenesismentioning
confidence: 99%